Pelatihan Pengenalan Dasar Virtual Reality Tour dalam Pengelolaan Media Promosi Objek Wisata di Desa Wisata Sidomulyo Kecamatan Silo Kabupaten Jember - Syah Riza Octavy Sandy; Icha Cahyaning Fitri (Universitas 45 Surabaya, 2025)
The utilisation of digital technology in tourism promotion plays a vital role in increasing competitiveness and visibility in the tourism industry. Sidomulyo Tourism Village, located in Jember Regency, faces challenges in promoting its tourism potential due to limited use of digital media. This community service programme provides an innovative solution through training on the introduction and development of Virtual Reality (VR) Tour technology as an interactive promotional tool. The activities include workshops, hands-on practice in creating VR Tour content, and continuous technical mentoring conducted by a team of experts. The training aims to enhance participants’ knowledge and skills in using digital media, especially in producing immersive virtual experiences that can attract visitors. The results show that participants’ understanding of VR technology has significantly improved, and they are capable of producing simple VR Tour prototypes independently. In addition, this programme encourages collaboration between village tourism managers, the local community, and IT practitioners to develop sustainable digital-based promotional content. The implementation of the VR Tour is expected to increase tourist visits, strengthen the digital branding of Sidomulyo Tourism Village, and serve as a model for other tourism villages in Jember Regency.